The Effect of Neck Mobilization Vs. Combined Neck and Lumbar Mobilization on Pain and Range of Motion in People With Cervical Disc Herniation: a Randomized Controlled Study - Ozdincler, Arzu; Aktas, Dogan; Reyhanioglu, Duygu Aktar; Ozturk, Basar; Aktar Reyhanioglu, Duygu (Elsevier, 2025)
Background: To assess the effectiveness of Kaltenborn-Evjenth Orthopedic Manual Therapy (KEOMT) applied to cervical-only mobilization versus both lumbar and cervical regions on pain intensity and range of motion (ROM) in individuals with cervical disc herniation. Methods: Thirty-three participants were enrolled in the study. The patients were randomly assigned to two groups. Group A received cervical-only KEOMT, while Group B received combined lumbar and cervical KEOMT. Interventions were administered three times a week for four weeks. Pain was measured using the Visual Analog Scale (VAS), ROM was assessed for flexion and lateral flexion, and Neck Pain and Disability Index (NPDI) and Short-Form 36 Health Survey (SF-36) were used for evaluation. Results: In intra-group measurements, a statistically significant difference was observed in all parameters of pain, ROM, disability, and quality of life for the mobilization methods applied in both groups (p < 0.05). Group B demonstrated significantly greater improvements in ROM/flexion, pain, and disability outcomes compared to Group A in inter-group measurements (p < 0.05). Physical and emotional sub-groups of quality of life measures also favored Group B in intergroup analysis (p < 0.05). However, the power values for ROM and quality of life parameters were found to be low. Conclusions: The cervical plus lumbar KEOMT technique is more effective than cervical-only mobilization in improving pain and disability. However, low power values for ROM and quality of life suggest these results may lack clinical significance, warranting further research.
Keywords: Intervertebral Disc Displacement; Musculoskeletal Manipulations; Range Of Motion; Articular; Neck Pain